0278 Work related characteristics of lung cancers among male construction workers: focusing on occupational cancer surveillance data in korea, 2011–2016. (21st August 2017) - Seo, Bo Reum; Kim, Yoon-Ji; Kang, Dongmug; Kim, Jong-Eun; Kim, Young-Ki
Abstract : The aim of this study is to examine occupational characteristics, hazardous work types and exposed substances in lung cancer in the construction industry by using data of occupational cancer surveillance at the national level in Korea. From 2011 to 2016, there were 6418 patients with lung cancer were registered through the Occupational Cancer Surveillance. Among them, the F class of the Korean Standard Industrial Classification and male sex were a total of 580 patients. Work relatedness was divided into 'High' and 'Low'. Focusing on work relatedness, 19.0% were high and 81.0% were low. There was no difference in the distribution of work relatedness and age groups (p=0.525) and total smoking amount (p=0.903) in lung cancers. There was a significant difference in the distribution of work relatedness and latency (p=0.019). The high prevalent 30 work types and 9 exposures high work relatedness in lung cancer. Painter of Painters (18.2%) were the most common hazardous material and job of followed by Crystalline silica in Elementary Workers (7.2%), and Crystalline silica in Stonemason (5.4%) in order. Lung cancer occurred at younger ages in construction workers compared to non-construction workers. Smoking has no relation with the work relatedness of lung cancer. It is necessary to manage work type and risk factors that are highly related to cancer in the construction industry.